Le soft power des entreprises marocaines opérant en Afrique : une revue de littérature systémique - EL-LABBAR Abdelghani; NECHAD Abdelhamid (African Scientific Journal, 2023)
In our comprehensive review of the soft power strategies employed by Moroccan companies in Africa, based on an analysis of 27 scientific articles, we explore how these companies enhance their presence on the continent. The study delves into the challenges they encounter, including heightened global competition and the associated political and economic risks in the region. This literature review contributes valuable insights for researchers, policymakers, and practitioners by offering a rigorous analysis of Moroccan companies' soft power in Africa. The findings align with broader research on corporate soft power, emphasizing the importance of a strong local presence, social responsibility, and culturally adapted communication for success. Recommendations include leveraging cultural heritage, understanding local dynamics, and forming partnerships. However, research limitations underscore a bias toward large corporations, while prospects advocate for further exploration of soft power mechanisms and effectiveness in diverse contexts. Practical implications for Moroccan companies in Africa involve developing a strong local presence, emphasizing social responsibility, adapting communication, forming partnerships, and investing in communication skills to bolster soft power and thrive in the African market.